Methodology for studying the efficiency of new structural and technological solutions for the restoration of building structures’ suitability for use - Tonkacheev , G.; Molodid , O. S.; Molodid, O. O. (Ways to Improve Construction Efficiency, 2023)
The article presents the developed, scientifically based methodology for introducing the construction practice of new structural and technological solutions for restoring building structures in reconstruction or capital repair conditions. This technique is based on the practical experience of surveying building structures, establishing the type and extent of damage, and the need for their reinforcement. The authors found that more than 70% of repair and restoration work on structures must be performed using classic technologies, 20% of cases require using existing modern methods, and almost 10% - develop new forms of repair and restoration work. In the publication, the authors present methods of researching the effectiveness of new structural and technological solutions for restoring the operational suitability of building structures. Experimental studies of new structural and technical solutions should be performed in several stages: laboratory and experimental model studies, by checking the results in real conditions at construction sites. A structural diagram of the research methodology of the latest and new structural and technological solutions for restoring the operational suitability of building structures has been developed, which offers a set of steps that allow, based on their results, to obtain new structural and technological solutions that can be applied in practice and have high quality. Each research stage of such solutions is characterized in detail, and a set of necessary elements is defined, allowing each stage to be implemented. In the case of the study of fundamentally new and complex structural and technological solutions for repair and restoration works of building structures, full-scale experimental studies are performed. It is assumed that such studies are carried out directly on single structures that need to be restored to operational suitability and subsequently observed during a certain period of operation. The developed methodology made it possible to carry out several research works. As a result, new constructive and technological solutions for restoring building structures were introduced into construction practice.